2009
DOI: 10.2478/v10001-009-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to wood dust and health effects on the respiratory system in a minor industrial estate in Bursa/Turkey

Abstract: Objectives: The aim of this study was to estimate occupational exposure to wood dust in the furniture industry in a minor industrial estate in Bursa/Turkey. Materials and Methods: The study was conducted between October 2006 and May 2007. In this study, a total of 656 persons, 328 woodworkers and 328 controls were included. A questionnaire was used in the study. Physical examination and the pulmonary function tests (MIR-Spirobank G) of the workers were performed. A portable Aircheck 2000 pump was used to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 25 publications
8
34
1
10
Order By: Relevance
“…The mean FEV1 and FVC values of woodworkers were significantly low, although the FEV1/FVC value was high. The results of this study indicated that exposure to wood dust adversely influenced the workers' respiratory functions, which supports the results of our study 18. Another recent study among 685 carpenters in Thailand showed significant negative correlations between mean dust exposure levels and FVC and FEV1/FVC%, but not FEV1, which suggests that wood dust exposure negatively affects lung function 19.…”
Section: Discussionsupporting
confidence: 90%
“…The mean FEV1 and FVC values of woodworkers were significantly low, although the FEV1/FVC value was high. The results of this study indicated that exposure to wood dust adversely influenced the workers' respiratory functions, which supports the results of our study 18. Another recent study among 685 carpenters in Thailand showed significant negative correlations between mean dust exposure levels and FVC and FEV1/FVC%, but not FEV1, which suggests that wood dust exposure negatively affects lung function 19.…”
Section: Discussionsupporting
confidence: 90%
“…We do not propose strong hypotheses about the role of other psychosocial stressors (e.g., effects of low job control, high job strain, high job effort/reward imbalance, and high emotional demands) in the development of obesity in firefighters because of a lack of preliminary investigations about the internal variation of these psychosocial stressors among OCFA firefighters. Nonetheless, based on the literature and our research [67,68] using the Midlife Development in the United States II dataset, these factors still need to be considered as possible risk factors for obesity in firefighters.…”
Section: Developing a Theoretical Framework On Work And Obesity In Fimentioning
confidence: 99%
“…2541 Chapter 2, Section 23 concerning the normal working hour, for not more than 8 hours a day. 17 The prevalence of respiratory symptoms among workers in wood furniture factory was 29.94%, the highest reported respiratory symptom was coughing (18.79%), followed by having sputum and sneezing (15.66% and 15.07% respectively). The scientific evidence indicated that when dust enter the respiratory tract, it could irritate the mucous membrane which lead to acute respiratory symptoms such as nose-itching, throat irritation, coughing, sneezing, sputum, 18 stuffy/running nose.…”
Section: 16mentioning
confidence: 99%